STRENGTH TRAINING FOR CHILDREN AND ADOLESCENTS (Fiep Bulletin - online, 2019)
The popularity of strength training among children and adolescents has grown more and more, a part of these youngpeople seek this activity because of health issues, as they lead a sedentary life, where the only activities are video games,computers and a super caloric diet, another part because they play sports such as soccer, fights and athletics, seek to improvetheir performance with gains in strength and muscular endurance, and still have those who are influenced by friends, society andthe media that value individuals with a healthy body. We Physical Education professionals should be especially attentive to theselast two groups, because in the eagerness to want a result in the short term it ends up seriously damaging their health. Studies ofthe American Academy of Pediatrics (1990), American College of Sports Medicine (1993), American Orthopedic Society forSports Medicine (1998) and National Strength and Conditioning Association (1996), which is supported by the American Collegeof Sports Medicine ), has shown that well supervised strength training for children and adolescents is effective and safe. (Fleck &Kraemer, 2006).
Keywords: Strength training; child; adolescent